Use of Botanicals as Environmentally Safe Management for Cotton Jassid - Siddiqua, TA; Miah, MRU; Amin, MR; Yesmin, K (Journal of Environmental Science and Natural Resources, 2017)
This study evaluated the efficacy of nine botanicals against cotton jassid on cotton variety CB 12. The nine botanical treatments were neem leaf extract @ 100 ml L-1 of water, turmeric powder @ 20 g L-1 of water, coriander powder @ 20 g L-1 of water, black pepper powder @ 20 g L-1 of water, chili powder @ 20 g L-1 of water, Garlic extract @ 100 g of grated and crushed garlic cloves per L of water, eucalyptus oil @ 5 ml L-1 of water, mahogany oil @ 5 ml L-1 of water, neem oil @ 5 ml L-1 of water. The botanicals were applied four times at 7 days interval during the cotton growing season. Among the tested botanicals neem leaf extract with 100 ml L-1 water and chili powder 20 g L-1 water after 24, 48 and 72 hours of application exerted the lowest jassid population. The botanical treatments have insignificant effect on the population of beneficials. The neem leaf extract with 100 ml L-1 water and neem oil with 5 ml L-1 water had greater effect on cotton jassid and revealed significantly lower levels of leaf infestation by number. Plots treated with neem leaf extract with 100 ml L-1 water and chili powder with 20 gL water resulted in significantly higher yield than that of the control. J. Environ. Sci. & Natural Resources, 9(2): 131-134 2016